Burden and features of neurological patients in Chittagong Medical College and Hospital in Bangladesh - Rahman, M. Ridwanur; Farhana Zaman; M. Hassanuzzaman; Akramul Azam; M. Mahabubul Alam Khandker; Tasbeen Akhtar Sheekha (International Journal of Research in Medical Sciences, 2023)
Background: Neurological disorders are a common and significant public health problem globally, and innovative strategies are needed to address the epidemic in resource-poor settings in Bangladesh. The aim of this study was to evaluate the burden and features of neurological diseases requiring hospitalization in a tertiary care hospital in Chittagong, Bangladesh. Methods: This study was a prospective observational study conducted from January to June 2021 on patients admitted to the adult neurology unit of a hospital in Chittagong, Bangladesh. Data was collected through face-to-face interviews, laboratory data, and previous medical records, and in-hospital complications and outcomes were recorded. The data was cleaned and analysed using SPSS and presented in tables. Results: In this study, stroke was the most common neurological condition requiring hospitalization, accounting for 74% of cases and leading to death in 73% of cases. The most frequent in-hospital complication was urinary tract infection (26%), mostly in stroke patients. Of stroke patients, 88% had incomplete recoveries at discharge, while 7% died. Hypertension was the most common risk factor present in both acute confusional state and stroke cases. The median duration of hospital stay was longest among patients with central nervous system infections. Conclusions: Stroke dominates the burden of neurological diseases requiring hospitalization in tertiary care hospitals in Bangladesh. The most frequent in-hospital complication was urinary tract infections, mostly in stroke cases. The overall in-hospital mortality was 7%, most patients recovered incompletely at discharge (82%).